The trouble with aid : why less could mean more for Africa - Glennie, Jonathan; International African Institute; Royal African Society; Social Science Research Council (U.S.) (London ; New York : Zed Books in association with International African Institute, Royal African Society, Social Science Research Council ; New York : distributed in the USA exclusively by Palgrave Macmillan, 2008)
Africa is poor. If we send it money it will be less poor. It seems simple. Jonathan Glennie argues that government aid to Africa actually has many very harmful effects. He claims that aid has often meant more poverty, more hungry people, worse basic services for poor people and damage to already precarious democratic institutions.
Time to think again -- The new aid era -- All aid's impacts: the bigger picture -- Pulling the strings: the reality of aid conditionality -- Institutions, institutions, institutions -- Aid, growth and confused academics -- A better future? -- Why is aid really going up? -- What is to be done?
Includes bibliographical references (p. 155-166) and index.
Keywords: Economic assistance -- Africa; Armut; Entwicklungspolitik; Entwicklungshilfe; Africa -- Economic policy -- 21st century; Afrika